NDF, ADF, AND Cellulose Content Of Tamarind Seed Hydroponic Fodder With Different Watering Volumes - Redempta Wea; Fransiskus Belo; Andy Yumina Ninu; Bernadete Barek Koten (JURNAL AGRIMENT, 2025)
The lack of ruminant feed sources requires the use of plantation waste in the form of tamarind seeds, which are abundant but limited in use due to the hardness of the seed coat and the presence of anti-nutrients. One solution is to use hydroponic fodder technology. The purpose of this study was to examine the NDF, ADF, and cellulose content of tamarind seed hydroponic fodder with different watering volumes. This study was conducted using a Completely Randomized Design (CRD) with 4 treatments and 6 replications consisting of R0 = 10 ml of water volume, R1 = 20 ml of water volume, R2 = 30 ml of water volume, and R3 = 40 ml of water volume. The variables in this study were the content of NDF, ADF, and Cellulose. Data analysis used Analysis of Variance (ANOVA) and Duncan's Advanced Test. The results showed that different water volumes in tamarind seed hydroponic fodder had a very significant effect (P <0.01) on the content of NDF, ADF, and Cellulose. It can be concluded that different water volumes have an impact on the NDF, ADF, and Cellulose content of hydroponic tamarind seed fodder.